Odzyskiwanie głosu. Ludobójstwo Ormian w Księdze szeptów Varujana Vosganiana. - Kowalski, Tomasz (Slavia Occidentalis, 2015)
The paper analyses Varujan Vosganian’s The Book of Whispers, a polyphonic novel that consists of various personal stories, many of which describe the Armenian genocide and its aftermath. Recalling some of them, it shows the ways the narrative speaks up for the memory of the victims who perished in the massacres and death marches of 1915 and 1916. The last part of the paper focusses on the relationship between Vosganian’s novel and the album published along with its Romanian edition (Cartea Şoaptelor. Album), containing, among other things, photographs of the victims and their mass graves. The narrator’s sense of being chosen to preserve their stories, heard from elders since early childhood, makes it possible also to discuss the novel in terms of Marianne Hirsch’s concept of post-memory.